Hydrogen-rich syngas production via steam reforming of palm oil mill effluent (POME) - A thermodynamics analysis - Cheng, Yoke Wang; Lee, Zhan Sheng; Chong, Chi Cheng; Khan, Maksudur R.; Cheng, C. K.; Ng, Kim Hoong; Hossain, Sk Safdar (Elsevier, 2018)
In current paper, thermodynamics study of palm oil mill effluent (POME) steam reforming was performed to investigate its feasibility for syngas production. By using the minimization of total Gibbs free energy method, the thermodynamic simulation is executed to study the effect of reaction temperature (573–1173 K) on product yield (Y i Y i) and syngas ratio (H 2: CO). Based on preliminary analysis, the POME liquor composed of 99.73% water and 0.27% organic contents by mole. Complete conversion of POME's organic contents is accomplished regardless of reforming temperature. However, the equilibrium constant reveals that not every organic constituent in POME are reformed into syngas via steam reforming at≤ 673 K, so their disappearance hints at the occurrence of thermal decomposition.